Development of Interactive Learning Media for Old Character Makeup in the Hair Styling and Fantasy Makeup Course - Puti Anggini, Saraskia; Supiani, Titin; Hidayah, Nurul (Journal of English Language and Education, 2025)
This study aims to develop interactive learning media for old character makeup in the Hairdressing and Fantasy Makeup course, in order to overcome the limitations of existing media and increase student engagement. The research and development (RD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was used in this study. The media was developed using the Canva application, and data was collected through a Likert-scale questionnaire from material experts, media experts, and students. The results showed that this interactive learning media was very feasible and practical. The validity test by the material experts obtained a percentage of 94.67%, and by the media experts 97.33%, both in the "Very Valid" category. Meanwhile, the practicality test by students through one-to-one trials reached 96% and small group trials reached 94.18%, both categorized as "Very Practical". Despite some limitations in the platform and interactive features, this product has proven effective in facilitating understanding and increasing student learning motivation. Thus, this interactive learning media for old character makeup is recommended as an alternative to support the learning process.